FRI0507 Dual Energy Computed Tomography for the Evaluation of Calcinosis in Systemic Sclerosis. (10th June 2014) - Hsu, V.M.; Bramwit, M.; Schlesinger, N.
Abstract : Background: Calcinosis, the deposition of calcified material in the skin and subcutaneous soft tissues, is frequently seen in up to 40% patients with SSc (1, 2). Calcium hydroxyapatite (3) is the major constituent of SSc-calcinosis. We used a new imaging modality, the dual-energy computer tomography (DECT) to study SSc-calcinosis. DECT is useful for assessing monosodium urate (MSU) crystal deposition in gout (4). Differences in attenuation enable differentiation between calcium hydroxyapetite and MSU crystals. Objectives: To examine clinical characteristics and patterns of systemic sclerosis (SSc) – related calcinosis of the hands using dual-energy computer tomography (DECT). Methods: 10 SSc patients with hand calcinosis had DECT of hands and wrists and their clinical information obtained. Results: Nine were females and 8 were Caucasians. Five had diffuse SSc. The mean age was 57 and mean disease duration was 19.4 years. DECT showed calcinosis most commonly in the subcutaneous fat pad of fingertips, along tendon sheaths, within the carpal tunnel, and adjacent to muscle groups. Two patients had extension (in sheets) into their forearms. Eight patients with bulky deposits also had advanced SSc- related organ complications, including ischemic digital ulcers, esophageal reflux and pulmonary fibrosis. Half of our cohort was disabled by SSc-calcinosis due to painful ulcers (100%), soft tissue swelling (80%), contractures (80%) new joint swelling (50%), or subsequent infections (40%). All had acro-osteolysis and 4 had bony destruction adjacent to the calcinosis. Conclusions: Calcinosis affects both diffuse and limited SSc and can be destructive in a subset of patients with bulky deposits, who typically have ischemic digital ulcers and advanced SSc organ complications. More studies are needed to better define calcinosis risk factors and the role of DECT in assessing SSc-calcinosis. References: Steen VD, Ziegler GL, Rodnan G et al, Clinical and Laboratory associations of anti-centromere antibody in patients with progressive systemic sclerosis. Arthritis & Rheum 1984;27 (2): 125-131 Elhai M, Guerini H, Bazeli R, et al. Ultrasonographic hand features in systemic sclerosis and correlates with clinical, biologic and radiographic findings. Arthritis Care Res 2012;64 (8):1244-1249 Freire V, Becde F, Feydy A, et al. MDCT imaging of calcinosis in systemic sclerosis. Clin Radiol 2013; 68(3): 302-309. Choi K, Al-Arfaj AM, Eftekhari A, et al. Dual Energy computed tomography in tophaceous gout. Ann Rheum Dis.2009 68 (10): 1609-1612. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1049